Estimation of virus-neutralizing antibody in microplates. Issue 1 (January 1973) - Pead, P. J.; Holley, A.
Abstract : A simple and rapid method for the titration of virus-neutralizing antibody is described. The micro-apparatus and reagents are readily available from commercial sources. Results are included from selected cases which illustrate various conditions of immune status and response.